KEPADATAN ULTISOL DAN HASIL JAGUNG AKIBAT PEMBERIAN BIOCHAR PELEPAH KELAPA SAWIT DAN MIKORIZA - Najati, Laila Tsalisa; Farni, Yulfita; Endriani (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Ultisol has a texture with a high clay content and a medium to high bulk density so it is susceptible to increasing soil compaction. High soil compaction indicates physical soil problems and inhibits plant growth. The application of soil amendments such as biochar and mycorrhiza can help be help improve soil compaction and support corn growth. This study aimed to examine the potential of biochar from palm fronds and mycorrhiza in improving Ultisol compaction and increasing corn yield. The research was conducted by using a randomized factorial design with 2 factors. The first factor was, oil palm frond biochar with 3 levels, no biochar (B0), biochar 5 tons.ha-1 (B5), and biochar 10 tons.ha-1 (B10). The second factor was mycorrhiza with 3 doses, without mycorrhiza (M0), mycorrhiza 10 grams (M10), and mycorrhiza 20 grams (M20). The results showed that the combination of oil palm frond biochar and mycorrhiza did not show an interaction in improving soil density, but had a significant effect on organic matter, plant height, and yield of maize plants. The application of biochar and mycorrhiza alone was able to improve the bulk density, soil porosity, penetration resistance and soil moisture content. The combination of 10 tons.ha-1 biochar and 20 grams mycorrhiza increased soil organic matter, plant height, and corn yield 66.74%, 24.77%, and 30.26%, repectively compared to the control. Thus, the combined application of oil palm frond biochar at 10 tons.ha-1 and mycorrhiza at 20 grams has the potential to improve soil organic matter content and increase corn yield.